The control of spectral and non-spectral interferences in ETAAS and TOF-ICP-MS - Husáková, Lenka (My University, 2019)
The presented work is organized as a commented collection of selected peer-reviewed scientific papers {A1-A17 } published between years 2005 and 2019. Research interests include the development of innovative methods for sample preparation and applications in electrothermal atomic absorption spectometry (ETAAS) {A1-A12} and inductively coupled plasma orthogonal acceleration time-of-flight mass spectrometry (oaTOF-ICP-MS) {A13-A17}. Specifically, the attention is focused on studying the matrix effects, developments of methods for their overcoming and applying of oaTOF-ICP-MS and ETAAS to the characterization of food, biological, geological, industrial and environmetal samples. The range of statistical methods was employed to have an integral role in both the interpretation and quality assessment of analytical results. Taking into consideration that modern approaches are looking for greener strategies, several methods employed in this work can be highlighted for moving towards green chemistry trends. Since all the discussed manuscripts are attached in the appendix, only background information, main achievements and general conclusions are discussed in the text.
Keywords: electrothermal AAS; high-resolution continuum source AAS; ICP-MS; interferences; analysis of biological samples; analysis of environmental samples; food analysis; analysis of industrial samples; microwave digestion; microwave extraction; design of experiments; statistical data analysis; AAS s elektrotermickou atomizací; AAS s kontinuálním zdrojem záření a vysokým rozlišením; ICP-MS; interference matrice; chemické modifikátory; mikrovlnná mineralizace; mikrovlnným polem asistovaná extrakce; analýza biologických materiálů a potravin; analýza průmyslových vzorků; analýza vzorků životního prostředí; plánování experimentu; statistické zpracování dat